Involvement of the 5-HT(1A) Receptors in Classical Fear Conditioning in C57BL/6J Mice - Stiedl, Oliver (J Neurosci, 2000)
The present study examined the involvement of the 5-HT(1A) receptors in classical fear conditioning using the 5-HT(1A) agonist 8-hydroxy-2-(di-n-propyloamino)tetralin hydrobromide (8-OH-DPAT) and the selective “silent” 5-HT(1A) receptor antagonist (N-[2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl]-N-(2-pyridinyl)cyclo-hexane carboxamide trihydrochloride (WAY 100635). The drugs were administered both subcutaneously and bilaterally into the dorsal hippocampus of male C57BL/6J mice. The training was performed in a single trial in which a tone was followed by a footshock. The retention of context- and tone-dependent fear was examined in separate tests conducted either 1 or 24 hr after training. Subcutaneous 8-OH-DPAT (0.1–1.0 mg/kg), when injected before but not after training, caused a dose-dependent impairment of contextual fear in both 1 and 24 hr tests, whereas tone-dependent fear was less affected. Pretraining intrahippocampal injections of 5.0 μg but not 1.0 μg 8-OH-DPAT caused a severe deficit in contextual fear when tested 24 hr after training. When injected both subcutaneously and intrahippocampally, 8-OH-DPAT induced the 5-HT syndrome, indicative of postsynaptic 5-HT(1A) receptor activation at the dose ranges that impaired fear conditioning. However, the behavioral changes induced by 8-OH-DPAT at the time of training could not account for inhibitory effects of 8-OH-DPAT on fear conditioning. Neither subcutaneous (0.03 mg/kg) nor intrahippocampal (0.5 μg per mouse) WAY 100635 altered context- or tone-dependent fear. However, subcutaneous WAY 100635 blocked both the 5-HT syndrome and the impairment of fear conditioning induced by subcutaneous or intrahippocampal 8-OH-DPAT. In contrast, intrahippocampal WAY 100635 blocked the impairment caused by intrahippocampal but not subcutaneous 8-OH-DPAT, indicating the involvement of extrahippocampal 5-HT(1A) receptors in fear conditioning. It is concluded that the deficits in fear conditioning induced by 8-OH-DPAT are a result of postsynaptic 5-HT(1A)receptor activation that interferes with learning processes operating at acquisition but not consolidation. Furthermore, the dorsohippocampal 5-HT(1A) receptors play an important but not exclusive role in the limbic circuitry subserving contextual fear conditioning.